Exploring the roles of special schools' principals in teacher quality improvement: A case study of special schools - Sahuddin, Muhammad; Jinkuan, Cheng; Verawati, Verawati (International Journal of Education and Learning, 2023)
Concern about the role of school principals in improving the quality of special schools remains one of the challenges in realizing better quality education in Indonesia. However, some obstacles to the role of the principal in improving the quality of special schools still exist. Principals of special schools are still faced with obstacles to improving school quality, such as the quality of teachers. Therefore, this qualitative study aims to explore the role of the principal of the Southwest Aceh public special school in improving teacher quality. In particular, it discusses the main challenges faced by the Southwest Aceh public special school principals and the roles and strategies they use to improve teacher quality. This qualitative research is to investigate the role of the head of the Southwest Aceh public special school in Indonesia, asking the main research question, what is the role of the principal in improving teacher quality? This research was conducted using a case study design. Data was collected through in-depth interviews with school principals, observation, and secondary data, including official documents and existing literature on the role of school principals. Data analysis was used using data analysis techniques according to Miles and Huberman: data collection, data presentation, data reduction, and conclusions. The interconnected theoretical framework built through the role of the principal and the theory of quality improvement is the most suitable because it helps to understand the experience, working conditions, and challenges of exploring the role of the principal in improving school quality critically. The research findings reveal the role of the school principal in improving the quality of teachers; that is, the principal conducts guidance, coaching, and supervision, grants study permits for schools to a higher level, and conducts training to increase teacher competence. Besides that, the principal explores new ideas from teachers according to the times in the world of education and creates harmonious relationships, openness, adjustments to the curriculum, division of teaching tasks or additional assignments, and differential learning, and provides rewards and punishments to teachers who break the rules. In giving the workload of main tasks and additional assignments to teachers, the average is high, and the school program is not related to each other.